Rational management of water resources in the basin of a big river is not easy - Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Throughout history, many times did floods in the river valleys of the East Mid-European Lowland occur. They brought about material losses and frequently generated hazards to human health and life as weII. For centuries now, human communities have been building up flood banks in order to protect themselves against the negative impact of floods. The results of investigations into the flood banks along the Odra river, which were made during and after the great flood of the year 1997, point out to the necessity of their renovation. The outcome of the research work carried out in Poland may be used for the renovation and reconstruction of old flood banks and for the construction of new ones in the whole area of the East Mid-European Lowland.
Keywords: Odra; wały przeciwpowodziowe; monitoring; gospodarka wodna; Odra River; river valley; flood banks; water management